Assessment of the sources and health risks of heavy metals in the soil-rice system based on positive matrix factorization and Monte Carlo simulation - Tong, Lei; Yang, Aoran; Fan, Mingyue; Wang, Dan; Liu, Yi; Huang, Xiangqiang; Xiang, Lian; Fu, Rongsheng; Cheng, Longfeng (Frontiers in Environmental Science, 2025)
In recent years, the harmful effects of heavy metal pollution in soil and rice on public health have garnered widespread attention. However, most studies focus only on the evaluation of heavy metal pollution in either soil or rice, often overlooking the fact of the combined effects of heavy metal pollution. We conducted an integrated assessment of the heavy metal pollution levels in both soil and rice. This study examined eight common heavy metals (Cd, Ni, As, Cu, Hg, Pb, Cr, and Zn) within the soil-rice system of Wanzhou District, Chongqing City. We employed Positive Matrix Factorization and Monte Carlo simulation to identify the sources of soil pollution and assess associated health risks. The findings revealed an average Impact Index of Comprehensive Quality (IICQ) value of 3.60 for the soil-rice system, indicating a pollution level exceeding “slight pollution”. The primary contributors to soil heavy metal contamination were identified as metal smelting and processing, pesticide and fertilizer use, manure application, geological background and rock weathering, agricultural activities, and coal combustion. Among the assessed metals, As, Cr, Cd, and Ni posed the greatest health risks and should be prioritized for monitoring and control. Given the heightened health risks associated with prolonged consumption of rice contaminated by heavy metals, addressing pollution in the agricultural soil-rice system is an urgent necessity.